Portal vein embolization in intrahepatic portal vein injury after blunt trauma: a case report - Sung Hoon Cho; Sang Yub Lee; Jung Geun Cha; Jihoon Hong; Sangcjeol Lee; Kyoung Hoon Lim (Journal of Trauma and Injury)
Mortality from hepatic injury has declined over the last several decades for various reasons, including nonoperative management, such as angioembolization, in more than 80% of cases. Conversely, surgical treatment is preferred in intrahepatic portal vein injury due to several reasons. Here, we report a case that treatment of blunt traumatic liver injury accompanied by intrahepatic portal vein injury through portal vein embolization. A 29-year-old female patient was transferred to our trauma center for vehicular accident injuries. Contrast-enhanced abdominal computed tomography showed a massive hemoperitoneum and liver laceration (grade IV) with contrast extravasation suspected of the right portal vein branch but no other organ injury. Since vital signs were stable, we decided to perform nonsurgical radiologic intervention. Portography showed active bleeding of the posterior branch of the right portal vein. A pseudoaneurysm in the portal vein was embolized through percutaneous transhepatic portal vein puncture. On follow-up liver dynamic computed tomography performed 2 days after embolization, the posterior branch of the right portal vein was sufficiently embolized, and no liver parenchymal necrosis was observed. The patient was discharged without any complications 2 weeks later. This report suggests portal vein embolization as a good alternative treatment method for portal vein injury in patients with stable vital signs.